Reflections from COVID-19 Pandemic: Contact Diary for Assessing Social Contact Patterns in Nepal - Shrestha, Niraj; Pandey, Achyut Raj; Angdembe, Mirak Raj (Journal of Nepal Health Research Council, 2020)
Management of COVID-19 in Nepal will certainly benefit from the experiences of other countries. However, they are less likely to be suitable for Nepal both in terms of context and resource availability. Social contact pattern studies have shown that understanding the nature of human-to-human contacts can help describe the dynamics of infectious disease transmission. The findings of such studies will help the country prepare itself for future outbreaks, inform mathematically modelling and public health interventions that match domestic capabilities. Methods such as self-reported contact diary can be used to conduct such studies following a feasibility study. Keywords: Contact diary;COVID-19; disease transmission; social contact pattern.